Comparison of DNA Extraction Methods in the Detection of Genetically Modified Foods Using Polymerase Chain Reaction - Nguyen, Chau Thanh Tung (2004)
Genetically modified organisms (GMOs) can be defined as organisms in which genetic materials have been altered in the way that does not occur naturally by mating or natural combination. According to Novel Food Regulation (EC/258/97, EC/1139/98, EC/49/2000, EC/50/2000 and EC/1829/2003), foods and food ingredients derived from GMOs are strictly regulated and are labeled mandatorily. Polymerase chain reaction (PCR) method is used to detect GM events in foods. The specific objectives of this study are to establish a sensitive, robust and rapid operation method for detection of GM events by using PCR and to conduct a preliminary survey for distribution of animal feeds and foods derived from GM events in both Malaysia and Vietnam. The two critical factors taken into account to achieve these objectives are applicability of different DNA extraction methods for each kind of samples and PCR amplification conditions. v Five DNA extraction methods (the Wizard method from Switzerland, the modified Wizard method with addition of beta-mercaptoethanol, the combination of Wizard and CTAB method, the CTAB method from Germany and the modified CTAB method with addition of beta-mercaptoethanol method) were optimized. The yield and quality of DNA obtained from raw soyabean, raw maize, animal feed, smooth tofu and soya milk samples were examined to determine the optimum method for each kind of sample. The results of comparative analysis showed that the CTAB method was the most optimal protocol for extracting total DNA from raw soyabean, raw maize and animal feed samples with 32.7, 28.4, 33.4 ng DNA/mg sample in yield, respectively. In addition, the DNA quality (the ratio of A260/A280 ranged from 1.9 to 2) was good enough not only for PCR amplification but also for DNA sequencing. However, the Wizard method was the best candidate for DNA isolation from smooth tofu (13.2 ng DNA/mg sample) and soya milk (3.4 ng DNA/mg sample) with relatively high quality of DNA (A260/A280 ratio was 1.7 and 1.9, respectively). The results of this survey showed that 20 out of 24 animal feed samples contaminated by at least one of three introduced genetic elements as promoter (P35S), terminator (NOS) and structural gene (EPSPS). In particular, all of the 16 animal feed samples from Malaysia and four out of eight animal feeds from Vietnam were GM-contaminant products. In contrast, neither soybean samples (12 samples) nor maize samples (24 samples) were positive with these assays. Therefore they were categorized as non-GM products. vi These results revealed that PCR amplification method provides the key advantages of high sensitivity, and robust and rapid operation whilst providing the requisites of careful experimental design that avoids both false-negative and/or false-positive results. Five primer pairs of LEC1/LEC2; ZE03/ZE04; P35S 1-5’/P35S 2-3’; HANOS118- F/HA-NOS118-R and EPSPS 1-5’/EPSPS 3-3’ chosen in this study produced the amplicons of 164, 277, 101, 118 and 118 base pair, respectively that fulfilled the product-size requirement and completed the whole detection procedure of GM events for raw soybean and raw maize as well animal feed samples. In addition, PCR amplification and DNA sequencing protocols presented in this study should provide a very useful tool for routine GM event detection in foods and feeds with regards to false-negative and/or false-positive results.